2018
DOI: 10.1111/codi.13822
|View full text |Cite
|
Sign up to set email alerts
|

Reduced risk of emergency admission for colorectal cancer associated with the introduction of bowel cancer screening across England: a retrospective national cohort study

Abstract: The start-up of bowel cancer screening in England was associated with a substantial reduction in the risk of emergency admission for CRC in people of all ages. This suggests that the roll-out of the programme had indirect benefits beyond those related directly to participation in screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…[22] Screening programs for CRC have furthermore been associated with a reduction in colon cancer cases diagnosed as an emergency. [23] Continuous monitoring and quality assurance of early detection and screening programs and detailed assessment of their impact on survival are therefore warranted. [24] Another phenomenon that has been proposed to explain differences in international stage distributions and stage-specific survival is stage migration.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Screening programs for CRC have furthermore been associated with a reduction in colon cancer cases diagnosed as an emergency. [23] Continuous monitoring and quality assurance of early detection and screening programs and detailed assessment of their impact on survival are therefore warranted. [24] Another phenomenon that has been proposed to explain differences in international stage distributions and stage-specific survival is stage migration.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence of reduced incidence associated with the introduction of population screening for bowel cancer. A large study [3] from England showed an adjusted odds ratio for emergency admission in patients diagnosed 6 months or more after commencement of screening was 0.83 (CI 0.76–0.90). Even with the improved accuracy offered by faecal immunochemical testing (FIT), the current approach misses cancers and contributes little to prevention.…”
mentioning
confidence: 99%
“…The effects of screening programmes have often been questioned; do patients attend, will it make us detect cancers earlier or even prevent cancer, will it prevent cancer specifi c deaths, and most of all will it also improve the overall mortality? [1] In this issue, Geraghty et al, performed an analysis of a national bowel cancer screening programme and looked to see if it could have an infl uence on the frequency of emergency admissions due to colorectal cancer [2]. Taking all patients with a new diagnosis of colorectal cancer in England during one year (n=27, 640) they and could show that the risk of being emergently admitted as an emergency had decreased from 6 months after the start-up of screening compared with patients not in a screening programme, adjusted odds ratio 0.83 (CI: 0.76-0.90).…”
mentioning
confidence: 99%